Consumer behaviour in the scratch card market: A double-hurdle approach - Jaunky, Vishal; Ramchurn, B. (2014)
This paper investigates how various socio-demographic as well as psychological factors are related to the purchasing frequency of Le Millionaire scratch card in Mauritius. In order to obtain a refined description and understanding of consumer behaviour, special attempts have been made to control for the personality traits of an individual. The OCEAN model of personality is thereby considered. We employ cross-sectional micro-data acquired from a household drop-off survey with a sample size of 1135 observations. Within a double-hurdle framework, gender, residential location, educational level, household income, alcohol consumption, other forms of gambling activities, and personality traits are found to be determining factors affecting an individual's decision to gamble in the scratch card market. Our findings help us to draw attention to the consequences of risk-taking behaviours and how personality-specific policies can be designed to influence gambling behaviour. © 2013 Taylor & Francis.